Path planning and optimization for micro-robot in a vessel-mimic environment - Huan, Zhijie; Ma, Weicheng; Wang, Jiamin; Wu, Feibin (Frontiers in Neurorobotics, 2022)
Manipulating micro-robots in blood vessels is an essential technology for medical researchers in applications such as drug delivery and thrombus removal. The usage of micro-robots in medicine can help overcome the limitations of many conventional clinical methods. In this study, we aimed to make the micro-robot more intelligent while moving through blood vessels. First, the skeleton of an image of the blood vessels is extracted, which is further used for path planning. Then, the skeleton-extraction-based A* algorithm was used for determining a best route for the movement of the microrobot at a safe distance from the vascular wall. Finally, the gradient descent algorithm was utilized to smooth the planned path. Simulations were conducted to verify the effectiveness of the proposed algorithms. The proposed methods would improve the efficiency for the further manipulation of the micro-robot in the blood vessel environment.